THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS AND ECONOMIC STATUS AND THE INCIDENCE OF STUNTING IN TODDLERS IN THE WORK AREA UPTD SIMPANG KIRI HEALTH CENTER SIMPANG KIRI DISTRICT SUBULUSSALAM CITY IN 2024 - Nophia, Ricca; Rizka Sititah Rambe; Fitriani Bancin, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Stunting is a condition when a child's height is shorter than the standard age due to long- term malnutrition. Based on the Indonesian Nutrition Status Survey (SSGI) of the Ministry of Health, the prevalence of stunting among children under five in Indonesia reached 21.6% in 2022. Subulussalam City is the area with the highest stunting prevalence in Aceh in 2022, reaching (47.9%). The purpose of this study was to determine the Relationship between Nutritional Status and Economic Status with the Incidence of Stunting in Toddlers in the Working Area of the Simpang Kiri Health Center, Simpang Kiri District, Subulussalam City in 2024. The type of research used in this study is correlational analysis with a cross sectional approach using primary data and secondary data. The population in this study is all toddlers who are stunted as many as 225 toddlers in the Working Area of the UPTD Simpang Kiri Health Center, Subulussalam City in 2024. The sampling technique in this study uses total sampling. The measuring tool used is a questionnaire. Based on research conducted using the Chi Square test with a confidence level of 95%, the results were obtained namely nutritional status (0.000<0.05), and economic status (0.000<0.05), which means that there is a significant relationship between nutritional status and economic status with the incidence of stunting in the Working Area of the UPTD Simpang Kiri Health Center, Subulussalam City in 2024. It is hoped that health workers can further improve the quality of midwifery services, especially counseling about stunting in toddlers with the message ABCDE, A (Actively take tablets to increase blood), B (Pregnant women regularly check pregnancy at least 6 times), C (Consume enough animal protein), D (Come to the Posyandu every month), E (Exclusive breastfeeding for 6 months).